Karakteristik Penderita Diare pada Balita Yang Dirawat Inap di RSUD Tabanan Periode 2020 - 2021 - I Nyoman Agung Triana Putra; Ni Kadek Elmy Saniathi; Putu Arya Suryanditha (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Tabanan Regency is one of the areas in Bali Province with a high case of diarrhea in children under five years old. The incidence of diarrhea in children is influenced by three risk factors: environmental, sociodemographic, and behavioral. This study aims to determine the characteristics of diarrhea in children under five who are treated at Tabanan Hospital in 2020 – 2021. This study uses a descriptive method with a cross-sectional design that uses secondary data from the hospital’s medical records. The subjects of this study were toddlers with diarrhea who were hospitalized at Tabanan General Hospital from 2020 – 2021. Sampling used a total sampling technique. The number of samples in this study was 55 toddlers. Data analysis in this study is univariate analysis. The results showed that the highest incidence of diarrhea occurred in the age group 1 – 12 months (45.5%), male (56.4%), and had normal nutritional status (96.4%). All toddlers had acute diarrhea (100%), mild-moderate dehydration (81.8%), most of them experienced diarrhea caused by an infectious process (81.8%), and as many as (69.1%) received antibiotics. The incidence of hypernatremia was 5.5%, and the remainder without complications, The length of treatment was primarily 1-3 days (56.4%).